Development of Multi-Phase Solid Formation for Dissolution Enhancement of Higher Drug Loading Phase-Separated Melt - Bolor-Uyanga Tumurbaatar; Hiroshi Takiyama (Journal of Chemical Engineering of Japan)
The method of Multi-Phase Solid with Shear (MPSwS), which uses shear force to form multi-phase solids, was investigated to evaluate the effect of changing drug loadings on the dissolution performance of API. Dissolution results showed that the dissolution rate monotonically decreased when the drug loading exceeded a certain amount. Therefore, a novel method was proposed to upgrade the MPSwS method and enhance the dissolution performance even with higher drug loading. The novel MPSwS&A method, which combined shear force and aeration, was used to form the pore structure in the solid. Dissolution results showed that the novel MPSwS&A method enhanced the dissolution rate. From the fractured surface of the solid, the pore structure caused by bubbles and the structure formed by fine crystalline particles were observed. These results suggest that the combination of shear force and aeration enhances API dissolution performance by the synergistic effects of forming micro and macro structures.